2011
DOI: 10.1016/j.cmet.2011.03.019
|View full text |Cite
|
Sign up to set email alerts
|

FGF15/19 Regulates Hepatic Glucose Metabolism by Inhibiting the CREB-PGC-1α Pathway

Abstract: Summary Regulation of hepatic carbohydrate homeostasis is crucial for maintaining energy balance in the face of fluctuating nutrient availability. Here, we show that the hormone fibroblast growth factor 15/19 (FGF15/19), which is released postprandially from the small intestine, inhibits hepatic gluconeogenesis, like insulin. However, unlike insulin, which peaks in serum 15 minutes after feeding, FGF15/19 expression peaks approximately 45 min later, when bile acid concentrations increase in the small intestine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
315
1
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 360 publications
(327 citation statements)
references
References 50 publications
10
315
1
1
Order By: Relevance
“…FGF15/19 is produced in the ileum, where its expression is controlled by the bile acid-activated nuclear receptor FXR, and subsequently is secreted into the circulation (22,23). In the liver, FGF15/19 suppresses bile acid synthesis and gluconeogenesis (22,24,25). Although we have not observed effects of FGF1 on bile acid homeostasis, it is possible that some of its metabolic effects are mediated directly through hepatic FGFR4 activation, because FGF1 acts as a universal ligand for all FGFRs.…”
Section: Discussioncontrasting
confidence: 40%
“…FGF15/19 is produced in the ileum, where its expression is controlled by the bile acid-activated nuclear receptor FXR, and subsequently is secreted into the circulation (22,23). In the liver, FGF15/19 suppresses bile acid synthesis and gluconeogenesis (22,24,25). Although we have not observed effects of FGF1 on bile acid homeostasis, it is possible that some of its metabolic effects are mediated directly through hepatic FGFR4 activation, because FGF1 acts as a universal ligand for all FGFRs.…”
Section: Discussioncontrasting
confidence: 40%
“…Besides positioning FGF19 as a selective agonist of insulin signalling (without promoting lipogenesis), Kir et al (184) demonstrated that Fgf15 (the FGF19 equivalent in mice)-null mice exhibited increased blood glucose concentrations after an oral glucose bolus. These studies suggest that FGF19 acts subsequent to insulin as a postprandial regulator of hepatic carbohydrate homoeostasis, utilising signalling pathways independent of insulin (183). In this regard, it is intriguing that FGF19 concentrations, in some studies, are lower in type 2 diabetic patients compared with control subjects (186,187).…”
Section: European Journal Of Endocrinologymentioning
confidence: 99%
“…A decade ago, Tomlinson et al (182) demonstrated, in transgenic mice, that FGF19 modulates energy and glucose homoeostasis. Most striking was the observation that FGF19 shares some metabolic actions of insulin, namely the stimulation of protein synthesis and glycogen synthesis (independent of insulin), and inhibition of gluconeogenesis (183,184,185). Besides positioning FGF19 as a selective agonist of insulin signalling (without promoting lipogenesis), Kir et al (184) demonstrated that Fgf15 (the FGF19 equivalent in mice)-null mice exhibited increased blood glucose concentrations after an oral glucose bolus.…”
Section: European Journal Of Endocrinologymentioning
confidence: 99%
“…FGF19 and FGF21 are emerging as endocrine hormones since they showed novel roles in bile acid, lipid, and glucose metabolism [4][5][6]. In obese or diabetic animal models, administration of FGF19 and FGF21 led to beneficial effects on metabolism through increasing insulin sensitivity, energy expenditure and white adipose browning [7][8][9][10].…”
mentioning
confidence: 99%